Correct implementation of agent interaction protocols - Bergenti, Federico; Egidi, Lavinia; Galliera, Leonardo; Giannini, Paola; Monica, Stefania (Frontiers in Computer Science, 2025)
Coordinating agents that communicate through asynchronous message exchanges to execute interaction protocols presents a complex and pressing challenge. In this article, we address this issue by introducing Multiparty Session Types (MPST) for the formal specification of agent interaction protocols, from which we derive implementations of the corresponding agent systems. Correctness is ensured on one side by the MPST methodology, which derives the local protocols of participants from a global specification by projection, and on the other by translating local types into agents, providing a proof that these agents behave as prescribed by the local protocols of participants. Our agent language is Jadescript, an agent programming language that targets the widely used JADE agent platform. In addition to the theoretical framework, we describe a prototype implementation of the related tools.